Theatre and state in France, 1760-1905 - Hemmings, F. W. J. (Frederick William John), 1920-1997 (Cambridge University Press, 1994)
Relations between theatre and state were seldom more fraught in France than in the latter part of the eighteenth and during the nineteenth century. The unique attraction of the theatre, the sole source of mass entertainment over the period, accounts in part for this: successive governments could not ignore these large nightly gatherings, viewing them with distrust and attempting to control them by every kind of device, from censorship of plays to the licensing of playhouses. In his illuminating study, F.W.J. Hemmings traces the vicissitudes of this perennial conflict, which began with the rise of the small independent boulevard theatres in the 1760s and eventually petered out in 1905 with the abandonment of censorship by the state. There are separate chapters on the provincial theatre, while the French Revolution is given particularly detailed attention. This work, complementing his earlier book The Theatre Industry in Nineteenth-Century France, will be of interest to students of theatre history, French studies and European culture in general.